IMPLEMENTASI MEDIA GAMBAR DALAM PEMBELAJARAN FIQIH MATERI WUDHU - Faishol, Riza; Wardani, Reza Wafi (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This research aims to find out the implementation of image media in the learning of class VII wudhu material fiqh at Ma'arif Genteng-banyuwangi Junior High School. This research is qualitative research. The type of research used in this research is field research (Field Resheach) which is directly involved in spaciousness research to obtain information related to the implementation of image media in the learning of class VII wudhu material fiqh at Ma'arif Genteng-Banyuwangi Junior High School which amounts to 2 classes. To find out the validity of data using the source triagulation technique. The techniques used for data collection use observation, interviews, and documentation. Data analysis techniques consist of data collection, data reduction, data presentation, and conclusions. From the results of this study, it can be concluded that, The Implementation of Image Media in the learning of Class VII Wudhu material fiqh at Ma'arif Genteng Banyuwangi Junior High School can be seen from the indicators of learning implementation from preparation, implementation of learning and evaluation. Learning to use image media at Ma'arif Junior High School Genteng_banyuwangi includes preparations such as compiling RPP, Prota, Promes and others. Likewise, the implementation of learning using image media and evaluation. All series of learning the implementation of the image media has been effective and innovated in its learning.